THE EXPERIENCES OF STAKEHOLDERS IN SUPPORTING THE IMPLEMENTATION OF THE MENTAL HEALTH COMMUNITY RECOVERY PROGRAM IN WEST JAVA PROVINCE INDONESIA - Gebi Elmi Nurhayati; Raden Bayu Kusumah; Bandu Murwasuminar (Belitung Raya Foundation, Indonesia, 2019)
Background: In general, mental illness poses the burden to the government, family, and community because of the patient’s low productivity and high-cost treatment. Recovery Based Program is a method to treat people with a mental health issue, which focus on the patient’s personal journey to have meaningful life despite the limitation of the illness. Several stakeholders of mental health have been trying to adopt it. Nevertheless, various problems arise at the time of the program execution. Objective: Purpose of this study is to obtain information regarding the experiences of stakeholder in recovery-based program implementation. Methods: Qualitative research with a phenomenological approach has been conducting. Five program holders from various institutions/organizations which running mental health program in West Java interviewed. Data were analyzed using Colaizzi’s method. Results: The result of this study revealed three themes: mental health services from stakeholder’s perspective, awareness of recovery, and efforts to overcome mental health challenges. Discussion: There is an urgency for enacting mental health regulation in a local scope, incorporating evidence-based practices into mental health programs and creating nursing homes for people with mental illness after being hospitalized at a psychiatric hospital. Conclusion: Mental health stakeholders encountered varied experience. However, they maintained an optimistic perception about Recovery Based Program for Mental Health in future.